033 Audit on the diagnostic pathway of patients with glioma mimics. Issue 12 (14th November 2019) - Joe, Dorothy; Lavrador, Jose; Vergani, Francesco; Gullan, Richard; Bhangoo, Ranjeev; Ashkan, Keyoumars; Finnerty, Gerald
Abstract : Background: Conditions such as primary CNS lymphoma (PCNSL) or demyelinating/inflammatory diseases may present with similar clinical and neuroradiological features to gliomas. These 'glioma mimics' are commonly diagnosed with brain biopsy, but this is not always possible. We aim to optimize the contribution of less invasive investigations to the diagnostic pathway. Method: Retrospective review of the diagnostic process of glioma mimics between September to November 2018 in a tertiary Neuro–oncology unit. Results: The Neuro-oncology MDT gave 558 opinions excluding post –operative reviews. Twelve cases were identified as glioma mimics. 6/12 were new cases. Further investigations in five new cases took 2.5 – 11 weeks to complete. Two patients deteriorated during diagnostic workup and had expedited brain biopsies which confirmed PCNSL. One proceeded with chemotherapy and one was referred to palliative care. Conclusion: Diagnostic tests prior to brain biopsy were not performed in all glioma mimic cases. This was because test results excluding brain biopsy were not available to start treatment before the patient deteriorated clinically. We anticipate that the frequency of glioma mimics will increase due to the greater use of immunomodulatory therapies. A dedicated protocol to achieve rapid diagnosis of glioma mimics is imperative to facilitate early, appropriate treatment.